Application of Realistic Mathematics Learning In Elementary School - Setyawati, Danik (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Mathematics subjects need to be given to students starting from elementary school to equip students with the ability to think logically, analytically, systematically, critically and creatively. In general, the approach to teaching mathematics still uses a conventional approach, students are only trained to work on problems and prioritize memorization rather than understanding. In addition, the learning process tends to be textbook and less related to everyday life, as a result, students do not understand mathematical concepts. Another factor that affects the process of learning mathematics is the stage of development of thinking in elementary school students is not yet formal or still concrete. Based on these problems, a learning model that is able to overcome them is needed, namely the realistic mathematics learning model (PMR), namely mathematics learning that is oriented to everyday experience and applying mathematics in everyday life. Realistic mathematics learning provides opportunities for students to find concepts in mathematics. Thus, realistic mathematics learning will have a very high contribution to students' understanding and students' thinking abilities.